THE INFLUENCE OF SERVICE QUALITY AND TICKET PRICE ON WINGS AIR AIRLINE PASSENGER SATISFACTION AT RAHADI OESMAN KETAPANG AIRPORT - Ahmad Mustofa; Maria Valeria Roellyanti (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
To implement the Wings Air service concept, currently Wings Air is still consistent with low cost carriers and provides services that comply with standards in every aspect as the basic foundation. This is not necessarily accepted as separate satisfaction by passengers who use this flight service, therefore this study aims to determine whether there is an effect of service quality and in-flight ticket prices provided by Wings Air on passenger satisfaction at Rahadi Oesman Ketapang Airport. The method used in this study is a purposive sampling approach and the research instrument is quantitative. The research tool is a questionnaire to 104 respondents. The test tool used is a partial simultaneous test. The results of this study can be shown with a significant value for each hypothesis, namely H1 6.742> 1.983; H2 3.856>1.983; H3 60.674> 3.09 means that based on the test results, the three hypotheses proposed, namely the relationship between service quality variables and ticket prices on passenger satisfaction variables, can be accepted.